Preparation of nanoporous graphene oxide by nanocrystal-masked etching: toward a nacre-mimetic metal–organic framework molecular sieving membrane. Issue 31 (21st April 2017) - Hu, Yaoxin; Wu, Yueqin; Devendran, Citsabehsan; Wei, Jing; Liang, Yan; Matsukata, Masahiko; Shen, Wei; Neild, Adrian; Huang, Han; Wang, Huanting
Abstract : A nacre-mimetic ZIF-8 molecular sieving membrane with well-aligned mesoporous GO was developed via nanocrystal-masked etching and bioinspired growth. Abstract : Ultrathin and robust metal–organic framework (MOF) molecular sieving membranes with high-flux and high-selectivity have shown great potential for low-energy gas separation. Here we report a controllable MOF nanocrystal-masked plasma etching method for forming evenly distributed mesopores on graphene oxide (GO) nanosheets. The resulting mesoporous GO/MOF nanosheets are used to synthesize an ultrathin polycrystalline MOF membrane with well-aligned mesoporous GO (MGO) nanosheets via a nacre-mimetic "assembly-and-intergrowth" approach. This is achieved by assembling the two-dimensional (2D) porous materials ( e.g. hybrid MOF/MGO nanosheets) into a laminate scaffold matrix, followed by the intergrowth of MOF crystals into this matrix. Such an approach enables the realization of homogeneous dispersion and alignment, strong interfacial binding, and interpenetration of porous GO nanosheets within the ultrathin MOF polycrystalline layer. In particular, this layered MOF/MGO membrane displays the improvement of the homogeneity in mechanical deformation and fracture resistance as compared to the polycrystalline MOF membrane, as shown by nanoindentation tests. In addition, the obtained MOF membrane with an ultrathin thickness of 430 nm shows excellent hydrogen separation performance (H2 /C3 H8 selectivity as high as 2409 with H2 permeances of 1.17 × 10 −6 mol m −2 s −1 Pa −1 ). Such a simple etching and bioinspired growth strategy could be potentially employed to produce other nanoporous 2D materials and nacre-mimetic polycrystalline films with unique properties for a range of advanced separation applications.